Dental health status and treatment needs among the adult population of western Indian city: a cross-sectional study - Modi, Yash; Desai, Tilomi; Mandanka, Srushti; Soni, Princy; Patel , Riddhi (International Journal Of Community Medicine And Public Health, 2024)
Background: Oral health is a key indicator for general health, overall well-being and quality of life. This study evaluated the oral hygiene knowledge, practice and its association with oral problems and create awareness about oral health, oral diseases and its treatment to the people in Ahmedabad. Methods: Sample size was estimated to be approximately 260 based on pilot study and by convenience sampling method. Chi-square test using SPSS statistical software. Results: It was observed that around 74.22% of participants felt tooth pain, of which female were more expressive of their pain as compared to their male counterpart. Of which a staggering 73.07% participants brushed their teeth only once in a day. It was observed that there was a failure among population to use interdental aids for cleaning and maintaining oral hygiene. Approximately 70% of population visited their dentist not even once in the year. Conclusions: It was observed and hence concluded on the basis of the derived results that there was a lack of appropriate oral health awareness among the local people in Ahmedabad even among the literate.